Amino acid profile and potential utilization purposes of albumin from four types of freshwater fish in Makassar, South Sulawesi, Indonesia - NURFAIDAH NURFAIDAH; ANDI NOOR ASIKIN; KASMIATI KASMIATI; ANGRAENI ANGRAENI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Nurfaidah, Asikin AN, Kasmiati, Angraeni. 2024. Amino acid profile and potential utilization purposes of albumin from four types of freshwater fish in Makassar, South Sulawesi, Indonesia. Biodiversitas 25: 4199-4207. Albumin, a high-quality protein, is known for its complete amino acid profile, which is essential for numerous biological functions, including immune response and nutritional status maintenance. This study investigates the amino acid composition of albumin in four freshwater fish species commonly found in Indonesia: Cyprinus carpio, Pangasius pangasius, Channa striata, and Trichopodus trichopterus to asses their potential utilization in sustainable food resources and nutritional and health-related products. Albumin extraction was performed using homogenization and incubation techniques, followed by amino acid analysis using High-Performance Liquid Chromatography (HPLC). The results revealed the presence of 18 amino acids, including 9 essential and 9 non-essential amino acids. The most abundant amino acids were glutamic acid, aspartic acid, leucine, and lysine, with lysine being particularly noteworthy for its role in wound healing and protein synthesis. Significant variations in the amino acid composition were observed across the species, influenced by factors such as diet, habitat, and species-specific physiology. Pangasius pangasius exhibited the highest lysine content (12.01%), while C. carpio had the highest glutamic acid content (24.55%) of total amino acid. These findings suggest that the albumin from these freshwater fish species is a valuable source of high-quality protein, with potential applications in developing nutraceuticals, functional foods, and dietary supplements aimed at improving health and nutritional status. Importantly, the study highlights the potential of these fish species as a sustainable source of protein, contributing to food security and supporting the development of affordable, protein-rich products that can enhance public health while reducing the reliance on conventional livestock-based proteins. This study provides new insights into the amino acid composition of fish albumin from Indonesian freshwater species, contributing to the broader understanding of the nutritional value of local fish resources and their role in promoting sustainable food systems.